Youth and Political Violence in Gombe state, North Eastern Nigeria: A Study of the “Yan Kalare” - Mohammed, Umar Bashir (Universiti Malaysia Sarawak (UNIMAS), 2017)
There have been several scholarly writings on political violence, particularly in relations to the sponsors, causes and consequences of political violence on the society. However, apart from the Nongovernmental organizations like Human Right watch and Amnesty International not much have been studied about the actors in political violence particular with regards to Kalare youth violence group in Gombe state, North Eastern Nigeria. Though, his study is an expansion of a previous study done by the same researcher in 2007, where that research concluded that Kalare youth were involved into activities of political violence as results of unemployment. While in an attempt by the Gombe government to eradicate the menace of Kalare violence in the state, the government has introduced two policies, one after the other to end the activities of Kalare violence in the state. Unfortunately, the two policies achieved limited success hence the activities of Kalare violence continue to persist.